Progressive Cerebral Small Vessel Disease Caused by an Autoimmune Response to Intravesical Bacille-Calmette-Guérin Treatment - Becker, Anouck; Grunwald, Iris Quasar; Unger, Marcus M.; Behnke, Stefanie; Spiegel, Joerg; Yilmaz, Umut; Walter, Silke; Faßbender, Klaus (Frontiers in Neurology, 2020)
Systemic BCGitis and autoimmune diseases are possible adverse events of intravesical Bacille Calmette-Guérin-(BCG)-instillations in the treatment of urothelioma cancer. We present the case of an 83-years-old male patient with rapid progressive symptoms of dementia up to mutism as well as tonic seizures. Immune-mediated cerebral small vessel disease was diagnosed and retraced to former instillations of BCG. Intense immunosuppressive treatment was performed and clinical restoration was achieved within several months. While cerebral vasculitis due to BCGitis has already been described before, this is to our knowledge the first case report to illustrate an immune-mediated small vessel disease after BCG-instillations. This should be considered in patients with rapidly progressive dementia-like symptoms treated with BCG, as an immunosuppressive treatment can be highly effective even at severe clinical stages.